2018
DOI: 10.5027/jnrd.v8i0.07
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Farmer’s Choice of Crop Production Response Strategies to Climate Change and Variability in Narok East Sub-county, Kenya

Abstract: Climate change is considered one of the most serious threats to sustainable development in the world. As a sector, agriculture is very dependent on climatic conditions, which makes it extremely vulnerable to the impacts of climate change and variability. The semi-arid areas of the world are especially more vulnerable to the impacts of climate change and variability. The purpose of this study was to determine how farmers adapt to changing climate in Narok East, and determine the factors that influence their cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The irrigation system allows rice farmers to control water, thereby alleviating the problems of drought and flood that are inherent threats in the other two production systems. In the same way, studies of Greig (2009), Kinuthia et al (2018), Buisson and Balasubramanya (2019), Ozaki and Sakurai (2020), and Thapa and Rahman (2021) found that water availability, particularly irrigation systems, is a key determinant of the choice of crops in Tanzania, Kenya, Tajikistan, Madagascar, and Nepal, respectively. Ozaki and Sakurai (2020) reported that the presence of irrigation in lowlands influence significantly and negatively the choice of upland rice production.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The irrigation system allows rice farmers to control water, thereby alleviating the problems of drought and flood that are inherent threats in the other two production systems. In the same way, studies of Greig (2009), Kinuthia et al (2018), Buisson and Balasubramanya (2019), Ozaki and Sakurai (2020), and Thapa and Rahman (2021) found that water availability, particularly irrigation systems, is a key determinant of the choice of crops in Tanzania, Kenya, Tajikistan, Madagascar, and Nepal, respectively. Ozaki and Sakurai (2020) reported that the presence of irrigation in lowlands influence significantly and negatively the choice of upland rice production.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, the binary Logit model results showed that factors such as experience in rice farming, age, and early sowing influence rice farmers regarding the abandonment of rice cultivation for the benefit of other crops. Kinuthia et al (2018) identified the factors influencing the choice of cropping strategies or practices in the face of climate change in Narok East Sub-County, Kenya, using the multivariate Probit model. The econometric model results showed that age, household size, education, land tenure, mean annual rainfall and onset of rains, and weather information were significant determinants in the choice of the strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the current study did not capture the income disparity of the respondents. On the other hand, studies by [21] showed that the Maasai community in Narok were not adopting crop diversification as a climate change adaptation strategy despite the current prevailing problems. Earlier studies by [9] stated that men opted for paid labour in urban centres as a way of livelihood diversification while women took up non-farm self-employed enterprises.…”
Section: Business Activities and Household Wellbeing Of Maasai Women ...mentioning
confidence: 99%
“…Despite long-term declines, and the effects of subsidised meat and milk products being dumped on African markets [17] , broadly favourable terms of trade still underpin successful pastoral economies [18] and [19], although drought or epidemic can precipitate rapid collapse into famine [20]. Similarly recent studies by [21] reported that farmers in Narok east sub-county are slow in embracing crop diversification as a strategy for climate change adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation